The UP varsity athletes perceptions toward the UAAP and unigames - Juliano. Ariel Primo L.; Uy, Gilda L. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2003)
This study aimed at analyzing the perceptions of the UP Varsity Athletes towards the UAAP Games and Unigames according to the nine aspects namely: level of competition (LOC), individual level of performance (ILOP), their team's level of performance (TLOP), level of preparation for the league (LOP), level of satisfaction in participation (LSP), level of motivation in participation (LMP), level of anxiety (LA),level of prestige of the league (LPL), and the level of organization of the games (LOG). More specifically, this study is aimed at comparing: all aspects of perceptions between UAAP and UniGames, each of the aspect of perception within each competition with respect to gender and sport,each of the aspect of perception between the UAAP and UniGames with respect to gender and sport, to determine the relationship among the nine aspects of perceptions within each competition, and of each aspect of perception within each competition according to gender and sport. Results of the study revealed that in comparing each aspect or perception between competitions, athletes view a distinction between the two games. Significant gender differences were revealed on the athlete's perception of one competition. Sport revealed different perceptions on these aspects. Also finding of this study have shown significant correlation among the aspects of perceptions, and relationships among these aspects do exist when athletes were asked to evaluate the competitions. It is recommended that the questionnaire be validated with further studies on other competitions the athletes participate in. Future in-depth researches could be investigated on the relationships of the different aspects of perceptions arising from this study. And further studies like these should be administered to varsity coaches as well.
"May 2003."
Thesis (M.S. Physical Education)--University of the Philippines Diliman
Keywords: College athletes -- Philippines -- Quezon City; Sports -- Psychological aspects